The role of independent commissioner in the effect of family ownership on capital structure in family companies in Indonesia - Rahmat Setiawan; Nunik Dwi Kusumawati (Universitas Hayam Wuruk Perbanas, 2020)
The purpose of this research is to analyze the effect of family ownership on capital structure with independent commissioner as a moderating variable in family companies in Indonesia. The study used the population consisting of family businesses listed on Indonesia Stock Exchange. The data were taken from the Indonesian Capital Market Directory (ICMD), financial statements, and annual report and the observation period was done from 2012 to 2018. The sampe was taken by a purposive sampling based the specified criteria. Based on the analysis result, it can be concluded that family ownership has a significant negative effect on capital structure. Independent commissionerweakens significantly the negative effect of family ownership on capital structure. Furthermore,firm sizehas a significant positive effect on capital structure, but profitability has a significant negative effect on capital structure.